Pendampingan Pembuatan Izin SPP-IRT Produk Keripik KWT Nine Seru Di Desa Lantan - Mulyawati, Sri; Efendy, Efendy; Fernandez, FX Edy; Nabilah, Sharfina; Halil, Halil (IAI Darussalam, 2023)
The Certificate of Fulfillment of Commitments for the Production of Processed Food for the Household Industry, abbreviated as SPP-IRT, is one of the legal documents that needs to be owned by MSME actors, especially those engaged in the Food Household Industry (IRTP). Chip products produced by KWT Nine Seru in Lantan Village do not yet have an SPP-IRT permit due to a lack of understanding of the procedures for making these permits. Therefore, the purpose of this service activity is to assist KWT Nine Seru in obtaining an SPP-IRT permit. The method of service activities consists of an initial survey of partner needs, socialization, assistance, monitoring, and evaluation. The results of the service activities showed that all participants were very enthusiastic about participating in a series of service activities, so the entire series of activities went well. KWT Nine Seru has an SPP-IRT license document that is valid until 2028. The importance of the results of this service activity is indicated by the usefulness of the business legality that has been issued, so that business actors can run their businesses safely and legally and can reach a wider market.